THE ROLE OF INCLUSIVE TEACHING IN ELEMENTARY SCHOOL PE AND HEALTH - Singh, Jaswinder; Ram Yadav, Mali (International Journal of Psychosocial Rehabilitation, 2021)
The goal of this study was to examine empirical studies conducted over the last two decades on the inclusion of physical education (PE) and make recommendations for future investigations. The review’s literature search was conducted in a methodical manner. Studies examined mostly used quantitative approaches as their primary data collection strategy. There were three common themes in the empirical research that we identified through a content analysis of descriptive data. Students with and without disabilities’ experiences with inclusive PE were examined in terms of stakeholder (teacher and parent) views as well as successful inclusive approaches. These research also shown that, despite the fact that social connections in inclusive PE can benefit students with disabilities, social isolation among students with impairments still remains. In the end, this study has given us a better understanding of the types of research that have been conducted in the field of inclusive PE for children with disabilities and some of their outcomes.